Performance determinants of higher education institutions and the mediating role of quality culture: internal auditors’ perspectives - Helmi Yazid; Lili Sugeng Wiyantoro; Tubagus Ismail; Iis Ismawati (Cogent Business & Management)
This research investigates the factors influencing the performance of higher education institutions (HEIs) audited by internal auditors from the perspectives of internal auditors at public universities in Indonesia. Internal audit scopes (IAS), professional skills (PS), organizational commitment (OC), applied procedure (AP), internal auditor experience (IAE), fraud prevention (FP), information technology (IT), ITIC internal controls (ITICs) and quality culture (QC) all have an impact on the performance of HEIs (PHEIs) audited by internal auditors. This research also looks at how internal quality auditing (IQA) influences QC, as well as how QC mediates the link between OC, procedure application (AP) and HEI performance audited by internal auditors. The sampling strategy employed in this research was random sampling, and the processed data consisted of 177 internal auditor samples gathered between January and June 2023. This study used structural equation modeling (SEM) and the SmartPLS statistical method. Our data show that PS, OC, AP, IAE, FP, IT, ITICs and QC all have substantial beneficial benefits on HEI performance audited by internal auditors, except for IAS, which has minor positive effects. IQA has a significant beneficial influence on QC. QC influences the link between OC, AP and HEI performance audited by internal auditors.